2006
DOI: 10.1016/s0022-5347(06)00315-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Success for First Stage Neuromodulation: Motor Versus Sensory Response

Abstract: A positive quadripolar test stimulation (greater than 50% improvement in symptoms) with InterStim sacral neuromodulation is more likely when intraoperative lead placement results in positive motor response vs only sensory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 11 publications
2
58
0
3
Order By: Relevance
“…Likewise, there was no association between loss of clinical response and specific diagnosis. Recent research has concentrated on identifying possible predictors for successful implantation and higher cure rates [25,26]. Further research is needed to ascertain if the failure to maintain the initial clinical response after stage II of the procedure might also represent a placebo effect in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, there was no association between loss of clinical response and specific diagnosis. Recent research has concentrated on identifying possible predictors for successful implantation and higher cure rates [25,26]. Further research is needed to ascertain if the failure to maintain the initial clinical response after stage II of the procedure might also represent a placebo effect in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…If only sensory response was elicited, just 4.7% of patients had a positive test, whereas 95% of patients with a successful test had a positive motor response. 35 Age Ͼ55 years has been reported to reduce the chances of success by ϳ30%, and more than three chronic comorbid conditions or neurologic disease also diminishes the odds of a successful response to neuromodulation. 36 The technique of percutaneous placement of a lead directly into the sacral nerve root foramen has the limitation of stimulating a single nerve root.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Cohen et al reported that motoric responses are superior to sensory responses in predicting clinical success so they recommend to perform permanent implantation solely when motoric responses were elicited. [8] Yet this is contradicted by data from the study of Govaert et al which showed that a correct position of the lead can be based on sensory responses alone, illustrating the importance of these sensory responses. [7] …”
Section: The Value Of Sensory Responsesmentioning
confidence: 96%